Phylogenetic relatedness within Neotropical fern communities increases with soil fertility - Lehtonen S; Jones MM; Zuquim G; Prado J; Tuomisto H (WILEY-BLACKWELL, 2022)
Main conclusionsOur results highlight the importance of edaphic variation in structuring plant communities over evolutionary time-scales. Within the tropical forests studied, the effects of soil variation on local phylogenetic community structure seem to outweigh those of climate. Several fern genera show strong edaphic niche conservatism to either poor or rich soils, whereas many other genera have radiated to span a rather broad edaphic range. PD-based measures are so dominated by deep relationships that genus-level phylogenies are sufficient to investigate these patterns in tropical fern communities.